2014
DOI: 10.1158/1535-7163.mct-13-0934
|View full text |Cite
|
Sign up to set email alerts
|

Coleusin Factor, a Novel Anticancer Diterpenoid, Inhibits Osteosarcoma Growth by Inducing Bone Morphogenetic Protein-2–Dependent Differentiation

Abstract: Coleusin factor is a diterpenoid compound isolated from the root of a tropical plant, Coleus forskohlii. Although Coleusin factor has been reported to suppress proliferation of and induce apoptosis in several types of cancer cells, the effects of Coleusin factor on osteosarcoma and the underlying mechanism are still not fully understood. In this study, we show that Coleusin factor treatment potently inhibits the growth of osteosarcoma cells associated with G 1 cell-cycle arrest. Interestingly, apoptosis and ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Geng and colleagues have shown Coleusin factor to inhibit osteosarcoma proliferation via BMP-2 upregulation and subsequent osteoblastic differentiation. The authors further demonstrated reversal of this effect with the addition of noggin, a BMP-2 inhibitor (27). Other investigators have reported that rhBMP both mitigates tumor growth and increases tumor predilection for apoptosis (28,29).…”
Section: Discussionmentioning
confidence: 87%
“…Geng and colleagues have shown Coleusin factor to inhibit osteosarcoma proliferation via BMP-2 upregulation and subsequent osteoblastic differentiation. The authors further demonstrated reversal of this effect with the addition of noggin, a BMP-2 inhibitor (27). Other investigators have reported that rhBMP both mitigates tumor growth and increases tumor predilection for apoptosis (28,29).…”
Section: Discussionmentioning
confidence: 87%
“…The ent-kaurene diterpenoid ent-16β-17α-dihydroxykaurane triggered apoptosis of MCF-7 cells by a decrease in telomerase mRNA (24). Oridonin, ponicidin, xindongnin A and xindoninin have been demonstrated to be potent inhibitors of NF-κB transcription activity (25). To investigate the possible mechanism for the anti-proliferative ability of GLA, the present study examined the DNA content of liver cancer cells by FCM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the researchers were able to reverse this effect with the addition of a BMP-2 inhibitor, noggin. [20] Other investigators have found that BMP reduces tumor growth and increases the tendency for osteosarcoma to undergo apoptosis. [21] These studies suggest that normal BMP-2 acts as an osteosarcoma inhibitor and may drive differentiation, apoptosis, or both.…”
Section: Discussionmentioning
confidence: 99%